ANALISIS KOMODIFIKASI KONTEN AL-QUR’AN DI INSTAGRAM PADA AKUN @QURANBASEDPLAY - Fithrah Lathifah (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
This article aims to analyze the commodification of Quranic content on the @quranbasedplay account using Vincent Mosco’s theory of commodification. This study is motivated by the observation that as Quranic education becomes accessible online, the Quran undergoes various transformations, one of which is the process of commodification. This is a qualitative study employing library research methodology. The primary data sources in this study are the Qur’anic posts on the @quranbasedplay account, while secondary sources include articles and books related to the topic of discussion. The data collection techniques used in this study are observation and documentation, and the data analysis technique is content analysis, supported by Vincent Mosco’s political economy theory, which focuses on the commodification of content. The results of this study reveal three key findings. First, the simplification of the Qur’an’s meaning in @quranbasedplay posts occurs when the meaning of each Qur’anic verse is not referenced from a tafsir (exegesis) but is directly linked to the post’s thematic objective. Second, the commodification of Qur’anic content occurs when Qur’anic surah or exegesis undergo a production process specifically, when a surah is packaged into an e-book containing interpretations of Surah al-Fatihah and a parenting curriculum, and when the second post on Surah al-Baqarah is divided into several themes to be discussed within the Qur’an Based Play Club. Third, the implication of the commodification of Qur’anic content is that the Qur’an no longer possesses only spiritual or utilitarian value but has shifted to having exchange or economic value.